Ivermectin in the management of a scabies outbreak in a long‐term care facility. (1st October 2021) - Walker, S.L.; Head, M.G.; Middleton, J.; Cassell, J.A.
Abstract: Linked Article: Bernigaud et al . Br J Dermatol 2021; 184 :1207–1209